2020
DOI: 10.3389/fcimb.2020.591172
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Extracellular Vesicles in Viral-Protozoan Symbiosis: Lessons From Trichomonasvirus in an Isogenic Host Parasite Model

Abstract: activities. These data support the concept that symbiosis with viruses may provide benefit to the protozoan parasite by exploiting sEVs as a vehicle for inter-cellular communications and modifying their protein cargo to suppress host immune activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…Our proteomics study has successfully identified TVV capsid proteins in sEVs released from T. vaginalis . Although Govender et al [ 25 ] could not identify any proteins of TVV origin in sEVs by LC-MS/MS, their experimental data supported the idea that viral endosymbiont may use sEVs as a vehicle for intercellular communications and deliver proteins to suppress host immune activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our proteomics study has successfully identified TVV capsid proteins in sEVs released from T. vaginalis . Although Govender et al [ 25 ] could not identify any proteins of TVV origin in sEVs by LC-MS/MS, their experimental data supported the idea that viral endosymbiont may use sEVs as a vehicle for intercellular communications and deliver proteins to suppress host immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear leukocytes increased their interleukin-6 (IL-6), IL-8, and tumor necrosis factor-α (TNF-α) output in response to sEVs from TVV-negative but not isogenic TVV-positive parasites. It is theoretically possible that sEVs may carry whole TVV virions or genomic dsRNA [ 25 ]. The TVV virions are at most 45 nm in diameter [ 40 ] and may fit into sEVs with a size of approximately 100 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of microorganisms as host symbionts is an important aim of the search for an explanation of the theory of infection; thus, it is an increasingly studied subject ( Hussa and Goodrich-Blair, 2013 ). Also, we intend to continue this research in order to clarify if microbiome represented by symbiosis predominantly between bacteria M. pneumoniae and B. burgdorferi with viruses induces release of small extracellular vesicles (sEVs) associated with abnormal cellular immune response, as described in the literature ( Christodoulides et al., 2018 ), and if these are present in the rejection episodes in morphomolecular studies of biopsies after CT ( Govender et al, 2020 ). These studies may support the concept that symbiosis with viruses may provide benefit to the main symbiont by exploiting sEVs as a vehicle for intercellular communications and modifying host immune response activation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, more than one TVV species can coexist in the same T. vaginalis cell ( Benchimol et al., 2002 ), and a high percentage of Trichomonasvirus in different protozoan isolates have been reported worldwide, ranging from 30% to 100% ( Fichorova et al., 2017 ), which may lead to the discrepancy of the findings. The implications of these co-infections so far are unclear, but evidence has shown that the TTV released from infected T. vaginalis cells induced inflammation upon treatment with metronidazole (MTZ) and may suppress host immune activation ( Fichorova et al., 2012 ; Govender et al., 2020 ). Each viral strain affects different aspects of the parasite.…”
Section: Prospects About Of Mucosa-associated Protozoa Infections Per...mentioning
confidence: 99%